2020
DOI: 10.1038/s41467-020-14372-3
|View full text |Cite
|
Sign up to set email alerts
|

A helitron-induced RabGDIα variant causes quantitative recessive resistance to maize rough dwarf disease

Abstract: Maize rough dwarf disease (MRDD), caused by various species of the genus Fijivirus, threatens maize production worldwide. We previously identified a quantitative locus qMrdd1 conferring recessive resistance to one causal species, rice black-streaked dwarf virus (RBSDV). Here, we show that Rab GDP dissociation inhibitor alpha (RabGDIα) is the host susceptibility factor for RBSDV. The viral P7-1 protein binds tightly to the exon-10 and C-terminal regions of RabGDIα to recruit it for viral infection. Insertion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 61 publications
2
45
0
1
Order By: Relevance
“…However, our understanding on the host factors responsible for RBSDV infection or plant defense is still limited. A recent report described that viral P7-1 recruited a host factor named Rab GDP dissociation inhibitor alpha (RabGDIα) for RBSDV infection in maize [2]. In this research, two copies of ZmAKINβγ, the regulatory subunit of SnRK1 complex were identified to interact with the P8 protein of RBSDV, and could respond to RBSDV infection in a similar response pattern.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, our understanding on the host factors responsible for RBSDV infection or plant defense is still limited. A recent report described that viral P7-1 recruited a host factor named Rab GDP dissociation inhibitor alpha (RabGDIα) for RBSDV infection in maize [2]. In this research, two copies of ZmAKINβγ, the regulatory subunit of SnRK1 complex were identified to interact with the P8 protein of RBSDV, and could respond to RBSDV infection in a similar response pattern.…”
Section: Discussionmentioning
confidence: 89%
“…However, a variety of diseases pose serious threats to maize production and quality. Among them, maize rough dwarf disease (MRDD) is a widespread and destructive viral disease worldwide [2,3]. It has been reported that the causal agents of MRDD in China are two fijiviruses (in the family of Reoviridae) including rice black streaked dwarf virus (RBSDV) and southern rice black-streaked dwarf virus (SRBSDV) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TEs of different types have been shown to alter gene splicing upon insertion. As an example, an Helitron insertion into a host susceptibility factor gene causes its alternative splicing leading to resistance to maize rough dwarf disease (Liu et al, 2020). Moreover, as noted above, TEs are the main target of epigenetic silencing, and therefore, the insertion of a TE within or close to a gene may bring the silencing machinery to this gene altering its expression (Zhang H. et al, 2018).…”
Section: Effects On Transposable Element Activitymentioning
confidence: 99%
“…Powstające skrócone roślinne białko GDI nie tworzy kompleksu z białkiem wirusowym. Dzięki temu rośliny kukurydzy niosące ten allel są odporne na pierwotną infekcję wirusem RBSDV [50]. TBSV (ang.…”
Section: Odporność Roślin Na Patogeny I Interakcje Z Mikroorganizmamiunclassified